Hubungan Lenght Of Stay (LOS) Dengan Tingkat Kepuasan Pasien Di Intalasi Gawat Darurat Puskesmas Rawat Inap GEBE - Dewiyanti; Dina Oktaviana; Alwi; Patmawati; Hamka; Kamriana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Length of Stay (LOS) is the amount of time nurses spend attending to patients in the A&E department, starting when the patient arrives and ending when treatment is complete. A long Length of Stay (LOS) in the emergency department is caused by the large number of patients congregating there without being attended to, which makes patients uncomfortable and causes them to spend a long time there, leading to patient dissatisfaction and a poor hospital reputation. Objective: This study aimed to determine the relationship between Length of Stay (LOS) and patient satisfaction levels in the Emergency Department at the Gebe Inpatient Health Centre. Method: The study design employed a descriptive-analytical method using a cross-sectional approach. The sample comprised 78 respondents. Data were collected using a validated questionnaire and analysed using Fisher’s exact test. Results: There is a significant correlation between Length of Stay and patient satisfaction in the Emergency Department at the Gebe Inpatient Health Centre, as determined by Fisher’s exact test, with a p-value of 0.000 < α 0.05. Conclusion: This study concludes that the Length of Stay (LOS) in the Emergency Department of the Gebe Inpatient Health Centre falls into the ‘short’ category and that patients are highly satisfied with the service received